Aron Aleksander Olizarowski and his Research Profile in the Opinions of the 19th Century Scientists - Niczyporuk, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Aron Aleksander Olizarowski’s opus vitae: De politica hominum societate is partially dedicated to the peasants’ question in Poland in the 17th century. His views were noted in the 19th-century Polish scholarly literature. Aloisio Luigi Capelli must have known Olizarowski’s work, since he presented the views expressed therein at scholarly meetings at the Vilnius University in 1817. Tadeusz Czacki repeatedly mentioned De politica hominum societate in his work entitled O polskich i litewskich prawach [On Polish and Lithuanian laws] and he also cited this work. This fact confirms the importance of Olizarowski’s views on the peasants’ question. Among other scholars, Feliks Słotwiński, Piotr Chmielowski, and Joachim Lelewel also mentioned De politica hominum societate in order to demonstrate Olizarowski’s original views on reforming the serfdom.